Models, Methods and Tools for Product Service Design The Manutelligence Project - Cattaneo, Laura; Terzi, Sergio (PoliMI SpringerBriefs, 2019)
Chapter 4 is available open access under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License via link.springer.com.